THE ANTICIPATION OF THE PSYCHOLOGICAL PARAMETERS BY APPLYING THE MATHEMATICAL MODEL FOR THE SWIMMER SPORTSWOMEN - Elena RATA; Risneac BORIS (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
In accordance with theory and in methodic of training, sports preparation aims at optimization and at the maximisation of the capacity to acquire sports performance by a long-term activity which assumes numerous means and specific techniques of intervention. Leaving idea that psychomotor preparation must be based on the incorporation of driving and mental functions, under the influence of the adulthood of the nervous system at the age of 14-16 years, we considered perform a study of the literature of speciality with the applicability of the psychological tests in the preparation of the sportswomen swimmers aiming at development psychomotor and psychological of concerned age